Nível de atendimento no relacionamento fornecedor-comprador: uma análise no mercado brasileiro de embalagens - Mazzo, Ricardo (2020)
The question that many companies would like to have the answer to is brought in this paper as the central point of the discussion: how to reach the level of service expected by a main customer? To reach this answer, twenty people were interviewed, ten suppliers and ten buyers, most of them linked to the Brazilian packaging market, the focus of this work. An action research methodology was implemented, given that the researcher experiences the buyer-supplier relationship daily in this market and the research conducted directly interfered in how one of the operations was structured. Cost, communication and adaptability have been listed as the main points of attention for suppliers who want to improve a relationship with a main customer. Many companies, both suppliers and customers, may use the following text as a basis for looking at business relationships in another way, proactively thinking about what builds competitive advantage for both sides while maintaining business sustainability.